Adoption of innovation among beef cattle farmers in Peninsular Malaysia - Abdullah, Farah Adila; Ali, Jamal; Zamzuri Noor, Mohd Saifoul; Ahmad Ghazali, Akmar Hayati (Human Resource Management Academic Research Society, 2021)
Cattle farming has become one of the engine growth in agriculture industry since years ago. The role of this sector is assumed as essential to supply protein source for the population. However, the problem arises when the import rate for beef is higher, and the supply has failed to meet the population's demand. Hence, the introduced innovation such as artificial insemination, integration and feedlot technique is seen as a driver that can further accelerate this sector. The cooperation and involvement from other parties, including the government and private sector are essential to ensure the successfulness of the introduced innovation. This study examines the socio-demographic profile and the adoption level of beef cattle farmers in four regions of Peninsular Malaysia. Multi-stage random sampling has been employed, and 233 farmers have involved as the respondents of this study. The farmers' average age is 48 years and had 13 years of experience in beef cattle farming. Most of the farmers found that they had a high level of innovation adoption, but certain of them face some obstacles such as financial and extension issues, which had hindered them from adopting innovation. The involvement of all stakeholders, including research centres, manufacturing and farmers, will benefit each other as the product can be supplied as the sample to enhance beef cattle production. Hence, a harmony and competitive situation can be created to ensure the food security of the country.